The Effect of Motivation and Discipline on Employee Performance at the Directorate of Samapta, Metro Jaya Regional Police - Salim, Agus Nur; Pratikno, Yuni; Kusuma, Sitta (Dinasti International Journal of Digital Business Management, 2026)
This study aims to analyze the influence of motivation and work discipline on employee performance, both partially and simultaneously, at the Samapta Directorate of the Jakarta Metropolitan Police. The focus of this study is important considering that the Samapta Directorate has a strategic role in maintaining public security and order and handling rapid responses to various operational situations, so that employee performance is highly determined by the level of motivation and work discipline they have. This study uses a quantitative approach with a census method, where the entire population of 89 employees is used as respondents. Data were collected through a structured questionnaire as the primary data, and supported by qualitative data in the form of open responses and limited interview results to enrich the understanding of empirical conditions in the field. Data analysis was carried out using SPSS version 27 software through validity, reliability, and hypothesis testing. The results of the study indicate that motivation (X1) and work discipline (X2) have a positive and significant effect on employee performance (Y) partially. In addition, the results of simultaneous testing indicate that motivation and discipline together have a significant effect on employee performance. The coefficient of determination (R Square) value of 0.337 indicates that 33.7% of the variation in employee performance can be explained by motivation and work discipline, while the remaining 66.3% is influenced by other factors outside the research model. This finding emphasizes the importance of strengthening motivation and work discipline in improving employee performance in police institutions.